Adaptation methods of the students physical education in the forming of young people culture of health - Kudelko V.E; Yakovenko Y.O; Korolinska S.V (Kharkov National Pedagogical University, 2011)
The survey results of motivation to physical education were described. The results of 50 first-year students of KhNUE were used, which indicate the lack of knowledge about level of the self culture of health; experimental research of the first year students motivation level to physical education was made. Was proved, that motivation is becoming more sustainable when use special actions for promoting adaptation process.